2012
DOI: 10.1016/j.foreco.2012.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of biological control of Gonipterus platensis (Coleoptera: Curculionidae) by Anaphes nitens (Hymenoptera: Mymaridae) in cold areas of the Iberian Peninsula: Implications for defoliation and wood production in Eucalyptus globulus

Abstract: a b s t r a c tSustainable management of forest plantations and cost-effective control strategies depend on previous estimations of the economic level of damage caused by the pests. The eucalyptus weevil, a key pest of Eucalyptus plantations worldwide, is mainly controlled using classical biological control, using the mymarid egg-parasitoid Anaphes nitens (Girault). Nevertheless, in several temperate regions, the parasitoid fails to reduce the weevil populations to economically sustainable levels. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 27 publications
0
56
0
1
Order By: Relevance
“…This is in part due to the considerable time and financial investment required to implement biological control programmes (including costly and uncertain scouting trips to identify natural enemies in the native range), and the introduction of stricter regulations for the import of biological control agents (Hajek et al 2016;this issue). In addition, for several species there is as yet no biological control available and for others the organisms introduced do no provide sufficient control, as with Gonipterus platensis by Anaphes nitens in the Iberian Peninsula (Reis et al 2012). These challenges have led to increased and more formalized global collaboration between eucalypt growers to share knowledge and biological control agents ).…”
Section: Spread For Example Guidelines Proposed Under the Internatimentioning
confidence: 99%
“…This is in part due to the considerable time and financial investment required to implement biological control programmes (including costly and uncertain scouting trips to identify natural enemies in the native range), and the introduction of stricter regulations for the import of biological control agents (Hajek et al 2016;this issue). In addition, for several species there is as yet no biological control available and for others the organisms introduced do no provide sufficient control, as with Gonipterus platensis by Anaphes nitens in the Iberian Peninsula (Reis et al 2012). These challenges have led to increased and more formalized global collaboration between eucalypt growers to share knowledge and biological control agents ).…”
Section: Spread For Example Guidelines Proposed Under the Internatimentioning
confidence: 99%
“…Their leaf consumption may decrease the growth of trees, negatively influencing their health condition, fecundity, and inhibiting regeneration (Rieske and Dillaway, 2008). The economic value of the wood losses due to reduced growth increases exponentially with the extent of defoliation (Reis et al, 2012), and may reach 310 $/ha/year (Lyytikainen-Saarenmaa and Tomppo, 2002). On top of these significant economic losses, regular insect outbreaks may trigger decline chains in the forests resulting in mass tree mortality (McManus and Csóka, 2007;Jepsen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mapondera et al (2012), the species present in Portugal is Gonipterus platensis. It is widespread in mainland Portugal Reis et al, 2012;Valente et al, 2017) Two specimens of the species complex were found in the Azores, one in a Malaise trap, the other on Erica azorica in a native forest area (Orom ı et al, Borges et al, 2013) …”
Section: Are Detection and Identification Methods Available For The Pmentioning
confidence: 99%
“…Severe defoliation implies loss of stem growth and important reduction of the volume of merchantable wood (Reis et al, 2012). E. globulus, E. viminalis and E. camaldulensis are indicated as the most vulnerable species (Cerasoli et al, 2016).…”
Section: Impactsmentioning
confidence: 99%